2021
DOI: 10.3390/ma14020349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mode II Fracture Toughness of Hybrid Fibrous Geopolymer Composites

Abstract: This research aims to examine the fracture toughness of hybrid fibrous geopolymer composites under mode II. For this purpose, eight geopolymer mixtures were cast and tested to evaluate the influence of steel and synthetic fiber hybridization on mode II fracture response. The first mixture was plain and was kept as a reference, while steel, polypropylene and glass fibers were used in the rest seven mixtures. The first three of which were mono-reinforced with one of the three fibers, while the rest of the four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Pictures for the disc specimens at room ambient temperature (R) and after exposure to 100, 200, 300, 400, 500 and 600 • C are shown in Figure 14a-g, both before and after impact testing. The fracture and failure of the reference unheated specimens align with what has been reported in previous studies [84][85][86][87][88] for plain concrete, where after a number of repeated blows, a small-diameter central fracture zone was created under the concentrated compression impacts via the top surface's steel ball. After a few more blows, the internal cracks propagated to the surface, forming a surface cracking of two or three radial cracks from the central fracture zone, which formed the failure shape that occurred after a few additional blows, as shown in Figure 14a.…”
Section: Failure Patternssupporting
confidence: 82%
“…Pictures for the disc specimens at room ambient temperature (R) and after exposure to 100, 200, 300, 400, 500 and 600 • C are shown in Figure 14a-g, both before and after impact testing. The fracture and failure of the reference unheated specimens align with what has been reported in previous studies [84][85][86][87][88] for plain concrete, where after a number of repeated blows, a small-diameter central fracture zone was created under the concentrated compression impacts via the top surface's steel ball. After a few more blows, the internal cracks propagated to the surface, forming a surface cracking of two or three radial cracks from the central fracture zone, which formed the failure shape that occurred after a few additional blows, as shown in Figure 14a.…”
Section: Failure Patternssupporting
confidence: 82%
“…The mixture of NaOH with Na 2 SiO 3 exhibits a higher concrete compressive strength than that of KOH with K 2 SiO 3 . FAs with a higher amount of CaO produce a higher compressive strength, particularly in the early ages [ 40 , 224 ]. According to an experimental study that involved the geopolymerization of 16 natural Si-Al minerals, the percentage of potassium oxide and calcium oxide in the raw material, as well as the molar ratio of Si-to-Al, the liquid alkali form, the degree of Si dissolution, and the molar ratio of Si-to-Al in a solution, have a significant impact on the compressive strength of AAMs [ 225 , 226 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Haist and Ferrara investigated the rheological properties of high-performance FRC during the mixing process and studied the influence of steel fibers on the rheological properties and concluded that thixotropic behaviors increase with the addition of steel fibers [47]. The distribution and orientation of the steel fibers also have an impact on the rheological behavior [25,[48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%